If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + x = 2x Solving 12 + x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + x + -2x = 2x + -2x Combine like terms: x + -2x = -1x 12 + -1x = 2x + -2x Combine like terms: 2x + -2x = 0 12 + -1x = 0 Add '-12' to each side of the equation. 12 + -12 + -1x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = 0 + -12 -1x = 0 + -12 Combine like terms: 0 + -12 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12
| 2x+10+4x+32= | | 4x+10-x=19 | | 9x^2-24x=-13 | | x^3=-52 | | 39/5/9 | | 2(3+6p)=30 | | 1(1.005)^12x=5/3 | | 3/5+22=28 | | -2*-5=x | | 3/5(1.005)^12x | | 15x+15=180 | | 4x^2+25x+47=0 | | 550000000=(b+425000)+b | | -8k=15 | | 2x+35=4x-1 | | -12*4=-32 | | 5=2(q+4)+3 | | 4(8-5h)=-8 | | 2-4(x-4)= | | -2/3v=-27 | | -2x=44 | | b/-7+1=-1 | | 8y-2=70 | | 12(z+3)=10 | | -20+8x=10x+20 | | 12(X-3)=10 | | y=x/9 | | 5x-5=x+20 | | y=6/x | | 85-(6n+8)=20 | | 6p+2(5p-3)-8p=26 | | 4.25=v^2/2850 |